Developmental plasticity of bacterial colonies and consortia in germ-free and gnotobiotic settings - Pátková, Irena; Cepl, Jaroslav J; Rieger, Tomáš; Blahůšková, Anna; Neubauer, Zdeněk; Markoš, Anton (BMC microbiology, 2012)
BACKGROUND: Bacteria grown on semi-solid media can build two types of multicellular structures, depending on the circumstances. Bodies (colonies) arise when a single clone is grown axenically (germ-free), whereas multispecies chimeric consortia contain monoclonal microcolonies of participants. Growth of an axenic colony, mutual interactions of colonies, and negotiation of the morphospace in consortial ecosystems are results of intricate regulatory and metabolic networks. Multicellular structures developed by Serratia sp. are characteristically shaped and colored, forming patterns that reflect their growth conditions (in particular medium composition and the presence of other bacteria). RESULTS: Building on our previous work, we developed a model system for studying ontogeny of multicellular bacterial structures formed by five Serratia sp. morphotypes of two species grown in either "germ-free" or "gnotobiotic" settings (i.e. in the presence of bacteria of other conspecific morphotype, other Serratia species, or E. coli). Monoclonal bodies show regular and reproducible macroscopic appearance of the colony, as well as microscopic pattern of its growing margin. Standard development can be modified in a characteristic and reproducible manner in close vicinity of other bacterial structures (or in the presence of their products). Encounters of colonies with neighbors of a different morphotype or species reveal relationships of dominance, cooperation, or submission; multiple interactions can be summarized in "rock - paper - scissors" network of interrelationships. Chimerical (mixed) plantings consisting of two morphotypes usually produced a "consortium" whose structure is consistent with the model derived from interaction patterns observed in colonies. CONCLUSIONS: Our results suggest that development of a bacterial colony can be considered analogous to embryogenesis in animals, plants, or fungi: to proceed, early stages require thorough insulation from the rest of the biosphere. Only later, the newly developing body gets connected to the ecological interactions in the biosphere. Mixed "anlagen" cannot accomplish the first, germ-free phase of development; hence, they will result in the consortium of small colonies. To map early development and subsequent interactions with the rest of the biospheric web, simplified gnotobiotic systems described here may turn to be of general use, complementing similar studies on developing multicellular eukaryots under germ-free or gnotobiotic conditions.
Keywords: Microbial Interactions; kultivační média; mikrobiální interakce; Serratia; Escherichia coli; Culture Media